2019
DOI: 10.5209/clac.64379
|View full text |Cite
|
Sign up to set email alerts
|

La concordancia de número en el castellano hablado por bilingües mapuzugun-castellano: “Y después ya cambió eso cuando aprendió a hablar wingka los mapuche”.

Abstract: Este trabajo estudia la discordancia de número en el nivel de la frase nominal y en el de la oración en el castellano hablado por hablantes bilingües de mapuzugun, usando el marco de la teoría del contacto lingüístico. La frecuencia de la discordancia de número en oraciones y frases nominales se determina a partir del análisis de un corpus de tres mil oraciones producidas por hablantes bilingües de los territorios de Lonquimay, Tranantue y Maquehue (Región de La Araucanía, Chile). El estudio muestra que aunque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…In this dynamic process, the adaptation of the BC can occur through different types of inconsistencies that appear in the systems, known as adaptations, or the change in the BC on some of its levels, known as modifications (Johanson 2008;Olate 2017;Olate et al 2019). This interactive process between BC and MC may take two directions: absorption or maintenance.…”
Section: Brief Theoretical Discussion Of Language Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…In this dynamic process, the adaptation of the BC can occur through different types of inconsistencies that appear in the systems, known as adaptations, or the change in the BC on some of its levels, known as modifications (Johanson 2008;Olate 2017;Olate et al 2019). This interactive process between BC and MC may take two directions: absorption or maintenance.…”
Section: Brief Theoretical Discussion Of Language Contactmentioning
confidence: 99%
“…Finally, the age considered for participation in this study was 45 years or older. This decision was made since in various sociolinguistic studies it is reported that the generation older than 40 years is the one that most commonly speaks the Mapuche language (Olate 2017; Olate et al 2019).…”
Section: Samplementioning
confidence: 99%
“…En el proceso de Copia ocurre la adecuación del CB a través de diversos tipos de diferencias dados entre los sistemas, lo que se conoce como Adaptación. También se da el cambio del CB en algunos o varios de sus niveles, conocido como Modificación (Johanson 2008, Olate 2017, Olate et al 2019, Olate y Pineda 2021, Hasler et al 2021 (Johanson 2002a, Olate 2017.…”
Section: Enfoques Teóricos Para El Estudio Del Contactounclassified
“…En Olate et al (2019) se estableció un procedimiento similar al que se ocupó en el tratamiento del género. El análisis consideró dos dimensiones vinculadas con el número gramatical del español: (1) el nivel de la frase nominal y (2) el de la cláusula.…”
Section: Númerounclassified